(3QSGdI aj GdYbGFOs - (3eLghds
(3ChdgG (B:s
(3ChdgG(B: (3Edi Cf jchf GdfGS CeI hGMOI aj GdcaQ Whd Gddg GdcGaQjf aj gPg GdOfjG HCf LYd Sba HjJ cd cGaQ ef aVI hcPG eYGQLg GdJj jQJbj YdjgGs
(3BNQgG (B:s
(3BNQgG(B: (3hjcaj aj dRhe GdeHGjfI dge Cfge CYdGe GdeNGdajf hbOhI Gdbhe GdVGdjf agDdGA GdPjf CKHJfGge aj gPg GdQSGdI CcKQ QDSGA GdHZj hQDS GdeHWdjf hCeG GdGJjGY hGdCPfGH adG fgGjI dge hdG jWeY aj MUQge hajeG PcQfGg ZfjI hcaGjI def CQGO WQjb GdQTGO hQZH aj GdfLs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds